Composition, diversity and association of pioneer plants on post-landslide areas in Palopo, South Sulawesi, Indonesia - DEWI MARWATI NURYANTI; LIANA LIANA; WITNO WITNO; ANDANG SURYANA SOMA; ASRIANNY ASRIANNY; SRIDA MITRA AYU; INDAH MIN AWALIA (Society for Indonesian Biodiversity, 2023)
Abstract. Nuryanti DM, Liana, Witno, Soma AS, Asrianny, Ayu SM, Awalia IM. 2023. Composition, diversity and association of pioneer plants on post-landslide areas in Palopo, South Sulawesi, Indonesia. Biodiversitas 24: 1862-1870. The existence of pioneer plants is very important because of their role in initiating vegetation succession as well as regulators of the physical properties of a disturbed environment. Landslide is one type of environmental disturbance that causes vegetation loss, either partially or entirely. In many cases, several pioneer plants start to appear following a landslide. This study aims to assess the vegetation composition, diversity and interspecific association of plant species in post-landslide areas in Palopo City, South Sulawesi, Indonesia. We employed sampling plot methods with a size of 5 x 5 m2 in 12 landslide sites with varying landslide characteristics during the period of 2021 to 2022. Vegetation composition was analyzed using Important Value Index and an interspecies association was analyzed using Chi-square analysis. The results of the study found that the pioneer plants on post-landslides consisted of a total of 112 species which can be classified into eight habitus, namely bamboo, herbaceous, vines, ferns, palms, shrubs, trees and bushes. Herbaceous plants had the largest number of species, with 53 species. Species with the highest IVI for tree was Trema orientalis (L.) Blume (79.86%), shrub was Homalanthus populifolius Graham (61.49%), bush was unidentified species (53.41%), fern was Nephrolepis cordifolia (L.) C.Presl (6.99%), vines was Merremia peltata (L.) Merr. (57.92%), herbaceous was Miconia papillosa (Desr.) Naudin (22.65%), while palm was Pandanus tectorius Parkinson ex Du Roi and bamboo was Bambusa balcoa Roxb. each had IVI of 200% because only one species was found. The results of the diversity analysis showed that trees, shrubs, bushes, ferns, vines and herbs had a moderate level of species diversity, while palm and bamboo had a low diversity level. Similarly, trees, shrubs, bushes, ferns, and vines had high evenness levels, while bamboo and palm had low evenness index. There were three associations between dominant plants, namely B. balcoa with T. orientalis, B. balcoa with H. populifolius, and B. balcoa with Macroptilium atropurpureum (DC.) Urb. The findings of this study suggest that in just one year, pioneer plants rapidly colonized post-landslide areas which provided vegetation cover for the open landscape.